DEFINIÇÃO DO CONCEITO E DOS COMPONENTES DE AVALIAÇÃO DE UMA SMART CITY UMA REVISÃO SISTEMÁTICA - Abreu, João Paulo Maciel de; Marchiori, Fernanda Fernandes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Since 2009/2010, the name "smart city" rose as a synonym of vanguard city. There are a lot of researches about this matter, and different definitions. Some concepts are focused in Information Technology and Communication (ITC), others in sustainability or a specific urban system such as energy or wastewater. However, it's too important a holistic view. A smart city could be a new city or an existing city that was changed, because smart cities promise: being more sustainable/efficient and solve common chronic urban problems. This paper aims to define the meaning of "smart city" using a bibliographic systematic review with the method SystematicSearchFlow (proposed by Ferenhof e Fernandes (2016)), bringing this wide view. Twenty-three publications are selected, with concepts and indicators, both holistic, and examples of smart cities and/or systems. As a result of the systematic review, this research shows an increase of scientific publications about smart cities in the last year. Most of these selected papers are from Asia, continent with the most quantity of mega-cities nowadays. This research shows that smart cities' concept is evolving and new challenges are predicted.